Baseline characteristics, disease severity and treatment history of patients with atopic dermatitis included in the German AD Registry TREATgermany - Heratizadeh, Annice; Haufe, E.; Stölzl, D.; Abraham, S.; Heinrich, L.; Kleinheinz, A.; Wollenberg, A.; Weisshaar, Elke; Augustin, M.; Wiemers, F.; Zink, A.; Kiedrowski, R. von; et al. (Journal of the European Academy of Dermatology and Venereology, 2019)
Background The Atopic Dermatitis (AD) TREATgermany registry was initiated by the German Society for Dermatology (DDG) in 2011 to evaluate the ‘real-life’ situation of health care for patients with AD. Objectives Interim data analysis on baseline characteristics as well as current and prescribed systemic treatments of the TREATgermany registry patients. Methods Patients (≥18 years) with moderate-to-severe AD [objective (o)SCORAD > 20], or with current or previous anti-inflammatory systemic treatment for AD within 24 months, were included and are followed up over at least 24 months. To assess clinical signs, the eczema area severity index (EASI, 0-72), the oSCORAD (0-83) and the Investigator Global Assessment (IGA; 6-point scale) were used. The disease severity was globally scored by the patients [Patient Global Assessment (PGA); six-step Likert scale]. Disease symptoms were assessed by the patient-oriented eczema measure (POEM, 0-28) and numeric rating scales (NRS, 0-10). Health-related quality of life was measured using the dermatological life quality index (DLQI, 0-30). Results A total of 612 patients were recruited across 32 sites between 06/2016 and 01/2019 (mean age: 42.6 ± 14.2 years; mean oSCORAD: 40.8 ± 16.3). The mean POEM score was 16.3 ± 7.5. Pruritus was rated highest among subjective symptoms (NRS: 5.4 ± 2.7). The mean DLQI value was 11.3 ± 7.5. The frequency of arterial hypertension was lower (20.8%) compared with the general population, whilst this was higher for depression (10%). More than 60% of the patients had received systemic glucocorticosteroids, and 36.8% had received cyclosporine A prior to inclusion. Dupilumab was the leading substance documented as either ‘current’ (12.1%) or ‘prescribed’ (31.4%) at baseline. Conclusions These ‘real-life’ data clearly demonstrate the substantial disease burden. Most of TREATgermany patients were already treated with or prescribed dupilumab at baseline. Moreover, current findings indicate the urgent need for further alternative agents in order to achieve a perceptible improvement of quality of life of patients with moderate-to-severe AD.
Gesehen am 21.04.2020